Identifikasi Proses Pengemasan Dan Saluran Distribusi Pemasaran Benih Jagung Hibrida Di PT. Soebandi Raja Agriculture - Rindani Ayu Sintia; Navita Maharani (Universitas Pahlawan Tuanku Tambusai, 2025)
The high demand for corn in the domestic market presents an opportunity for seed companies in Indonesia. PT. Soebandi Raja Agriculture is an Indonesian company that plays a key role in meeting the need for high-quality corn seeds. In the corn seed production process, in addition to seed quality, proper product packaging is also essential. Distribution channels are also crucial for a company. This study aims to identify the packaging process and marketing distribution channels for hybrid corn seeds implemented at PT. Soebandi Raja Agriculture. This study uses a qualitative approach conducted inductively to obtain comprehensive and in-depth data. Data collection techniques used observation and interviews. The results show that the hybrid corn seed packaging process is carried out manually with the help of simple tools such as digital scales and sealer machines. PT. Soebandi Raja Agriculture applies three distribution channel patterns: cooperation with the government, direct sales, and free market targeting.